2005
DOI: 10.1111/j.1365-2125.2005.02422.x
|View full text |Cite
|
Sign up to set email alerts
|

Should domperidone be used for the treatment of gastro‐oesophageal reflux in children? Systematic review of randomized controlled trials in children aged 1 month to 11 years old

Abstract: Aim  To determine whether there is robust evidence of efficacy for domperidone in reducing the symptoms of gastro‐oesophageal reflux (GOR) and gastro‐oesophageal reflux disease (GORD) in children. Methods  Systematic review of randomized controlled trials (RCTs). A search was made of the Cochrane Library Issue 2004 (Central Register of Controlled Trials and Database of Systematic Reviews), Medline (Pub‐med) 1966 to present and Embase from 1974 to 2004, and reference citations of the RCTs that had been found el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0
9

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(64 citation statements)
references
References 12 publications
0
55
0
9
Order By: Relevance
“…Desde a suspensão da comercialização da cisaprida, a domperidona passou a ser muito usada, sendo a droga pró-cinética mais usada em nosso meio. Pritchard et al constataram apenas evidências menores da eficácia da domperidona 60 .…”
Section: Situação Clínica Tratamentounclassified
“…Desde a suspensão da comercialização da cisaprida, a domperidona passou a ser muito usada, sendo a droga pró-cinética mais usada em nosso meio. Pritchard et al constataram apenas evidências menores da eficácia da domperidona 60 .…”
Section: Situação Clínica Tratamentounclassified
“…Other workers, in fact, have suggested that prokinetics increase gastroesophageal motility and facilitate emptying of the stomach by improving peristalsis and reducing pyloric tone. 15 This beneficial effect, however, was significant after the first drug administration only and was accompanied by an unexpected increase in reflux frequency. Actually there are insufficient safety data to explain these results.…”
Section: Discussionmentioning
confidence: 90%
“…Little, however, is known about its real efficacy and its contraindications, especially in newborns. 15 Aim of the present study was to evaluate the short-term effects of domperidone on GER in symptomatic newborns by means of the simultaneous measurement of impedance and esophageal pH.…”
Section: Introductionmentioning
confidence: 99%
“…They are not widely used for infants due to the side effects of the nervous system, such as metoclopramide, lethargy, irritability, gynecomasty, and tardive dyskinesia, and due to their short duration of effect (33). Domperidone is more frequently used due to its less central effects (34). There is a placebo-controlled trial in the literature indicating the recovery of esophagitis (1).…”
Section: Drugs Preventing Acidmentioning
confidence: 99%